2015
DOI: 10.1007/s00170-015-7391-9
|View full text |Cite
|
Sign up to set email alerts
|

A study to estimate the tensile strength of friction stir welded AA 5059 aluminium alloy joints

Abstract: Friction stir welding (FSW) is an important welding technique where in, and optimizing the process parameters will improve the joint strength of the welds. The FSW process and tool parameters play a major role in determining the joint strength. In this paper, an attempt has been made to establish an empirical relationship between the FSW process parameters (rotational speed, welding speed, and axial force) and predicting the maximum tensile strength of the joint. Statistical tools such as design of experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…Some researchers also used a square tool and reported a value of 211 MPa for a 700-min -1 tensile strength when welding aluminum alloys AA5383 and AA7075. 29 Similar tensile-strength values were obtained and reported for friction-stirwelded aluminum alloys.…”
Section: Tensile Examinationsupporting
confidence: 79%
See 1 more Smart Citation
“…Some researchers also used a square tool and reported a value of 211 MPa for a 700-min -1 tensile strength when welding aluminum alloys AA5383 and AA7075. 29 Similar tensile-strength values were obtained and reported for friction-stirwelded aluminum alloys.…”
Section: Tensile Examinationsupporting
confidence: 79%
“…Thus it can be concluded that mechanical properties of the welded samples the researchers using square tool is reported as 70 HRB for 700 min -1 Rockwell hardness value of welded aluminum alloys 5383 and 7075 alloys. 29 Similar kind of hardness values is obtained and researcher reported friction stir welded aluminium alloys.…”
Section: Hardnesssupporting
confidence: 74%
“…By contrast, the hardness within the weld area exhibits a decrease for all the three joints. During the FSW of cold-worked aluminum alloys, the welding heat enables annealing and recovery to take place, and hence induces the formation of softening region with lower hardness than BM [16][17][18]. Since some strength recovery has occurred in the nugget zone and thermo-mechanically affected zone due to the grain refinement strengthening and strain strengthening effects, as commonly confirmed in the FSW of other non-heat treatable aluminum alloys [2,6,9], the joints all have the lowest hardness zones at the HAZs.…”
Section: Joint Mechanical Behaviormentioning
confidence: 99%
“…Then, the microstructural examinations were carried out on those alloys [10] and [11]. Later, the process parameter optimization studies were reported on friction stir-welded aluminium and its alloys [12] and [13]; other studies including corrosion analysis and tensile strength optimization were also reported for aluminium [14] to [16] and magnesium alloys [17] but nowadays the research focus is on high-temperature materials. A feasibility study related to friction stir welding of mild steel was initially presented by Linert et al [18], in which defect-free welds were successfully produced, but excessive tool wear was reported; the paper emphasized the need to work on the geometry of the tool in order to eliminate the issue of tool wear.…”
Section: Introductionmentioning
confidence: 99%